If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2(x + -3) = -2(x + 1) Reorder the terms: 5x + 2(-3 + x) = -2(x + 1) 5x + (-3 * 2 + x * 2) = -2(x + 1) 5x + (-6 + 2x) = -2(x + 1) Reorder the terms: -6 + 5x + 2x = -2(x + 1) Combine like terms: 5x + 2x = 7x -6 + 7x = -2(x + 1) Reorder the terms: -6 + 7x = -2(1 + x) -6 + 7x = (1 * -2 + x * -2) -6 + 7x = (-2 + -2x) Solving -6 + 7x = -2 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -6 + 7x + 2x = -2 + -2x + 2x Combine like terms: 7x + 2x = 9x -6 + 9x = -2 + -2x + 2x Combine like terms: -2x + 2x = 0 -6 + 9x = -2 + 0 -6 + 9x = -2 Add '6' to each side of the equation. -6 + 6 + 9x = -2 + 6 Combine like terms: -6 + 6 = 0 0 + 9x = -2 + 6 9x = -2 + 6 Combine like terms: -2 + 6 = 4 9x = 4 Divide each side by '9'. x = 0.4444444444 Simplifying x = 0.4444444444
| 4(x+2)=3(x-5)+x | | x+9.1=1.4+9.1 | | x+3.2=7.7 | | x+1+7x=-15 | | x+9.1=4.1+9.1 | | -3-7=-4+x | | 9-(2n-6)=5-3n | | -7-3=8x+4-7x | | 1.4y=4.62 | | 9x+8-8x=13 | | X(2x+3)=(2x+5)(x-1) | | (x/50)=-11+25 | | x+12527=215+12527 | | 2+2.99999999999999999+0.1=n | | 6/5x^2+7x-70=0 | | -14+10=m-3 | | x-12527=215-12527 | | 2a+6=5a-30 | | 16(2x-1)=4(8x+9) | | 40-x=72 | | 2.561x=-12.36963 | | 2[7-5(1-n)]+5n=-6+2[6(n+1)-3n] | | 4y+y=6y-4y | | -(5x-3)-(4x-7)+6=-7(x-4)-(9x+5)+8 | | 8b+20=9b-6 | | 2x^3=384 | | (-3/-4) | | 4(x+5)=2(2x+1)+18 | | 1/4*(x+3)=4x-2(x-3) | | 13-(2f+2)=2(f-2)+3f | | 7(-4+6x)= | | 5x+17y=-13 |